Assessment of the spatial association network of green innovation: Role of energy resources in green recovery. (December 2022) - Liang, Zhiying; Chen, Jian; Jiang, Dayang; Sun, Yunpeng
Abstract: Green innovation is one of the latest topics of sustainable development, which has unknown dimensions that can be explored. The main purpose of this paper is to study the green innovation network among 144 countries through the Slacks-based measure of directional distance functions approach for annual data throughout 2017–2021. In addition, the Quadratic Assignment Procedures (QAP) analysis is used to determine the impacts of influencing factors on the green innovation efficiency of the examined sample of countries. The major findings revealed that the global green innovation network is centered in North America, Western Europe, East Asia, and Oceania. The results of the QAP technique confirmed that geographical proximity, good governance, consumption of fossil fuels in transportation, environmental regulation index, energy resources price system, the difference in Gross Domestic Product (GDP) per capita, and pandemic affect the formation of the spatial relationship network of green innovation efficiency. This paper recommends the most important practical implications of increasing the share of development and research in the green energy sector, improving green loans, promoting green financing tools, and prioritizing the digital economy. Highlights: The global green innovation network is centered in North America, Western Europe, and Asia-Oceania. Most countries of the Middle East and Latin America are classified as developing economies. The North American region is the heart of global green innovation. Geographical proximity, policy, transport, ERI, energy price system, development, and epidemic (the COVID-19 death) affect the formation of the spatial relationship network of green innovation efficiency.